PENGARUH SISTEM AKUNTANSI KEUANGAN DAERAH TERHADAP AKUNTABILITAS LAPORAN KEUANGAN PADA SATUAN KERJA DINAS PENDAPATAN DAN PENGELOLAAN KEUANGAN (DPPK) PEMERINTAH DAERAH KABUPATEN BANDUNG - Surjono, Welly; Nova Roslina Firdaus, Nova (Jurnal Riset Akuntansi dan Keuangan, 2017)
The purpose of this paper is to know the implementation of regional financial accounting system, the implementation of accountability of regional financial statements, and the influence of regional financial accounting system to accountability of local financial statements. The research used descriptive method with quantitative approach. Data analysis techniques used simple regression correlation, coefficient of determination analysis and t-student test. The result of the research shows that the correlation coefficient is 0.738, which means there is positive direction and strong influence level between the regional financial accounting system to the accountability of the regional financial report. The coefficient of determination (Kd) is 0.5446 or 54.46%, it can be interpreted that the local financial accounting system affects the accountability of local financial statements of 54.46%, and the rest of 45.54% influenced by other factors . Significant test obtained is t count equal to 8,885, with dk = 66 at ï¡ 5% obtained t table equal to 1,998, because> (8,885> 1,998), meaning Ho rejected and Ha accepted, so there is influence between financial accounting system of area to accountability report Regional finance.